Use of space for cultural activities in public libraries - Gallo-León, José-Pablo; Quílez-Simón , Pedro (Anuario ThinkEPI, 2024)
Cultural activities are carried out on a massive scale and eminently face-to-face in public libraries. The setting for these activities is diverse. As a result of a survey carried out in the Region of Murcia we found that, although most libraries have dedicated spaces, it is common to schedule them in areas intended for other uses, such as reading rooms. This seems to be related to the current concept of the library as a place, but also to the idea of the library as a sacred space. Either way, it demands that spaces are designed with these possibilities in mind, with adaptability as a goal.